THE ROLE OF CULTURE IN THE DEVELOPMENT OF LIBRARIES - Tojiakhmedova Muyassarkhon Khaydarovna (Bright Mind Publishing, 2025)
This article analyzes the role of libraries in modern society from the perspective of culture. The study highlights the importance of libraries not only as traditional knowledge centers, but also as institutions that preserve cultural heritage, form a multicultural environment, and operate globally using digital technologies. Based on specific examples from Uzbekistan and world practice, the digitization of cultural heritage, the combination of traditional and modern methods, as well as the socio-spiritual functions of libraries are considered.
Keywords: Library, cultural heritage, digitization, rare manuscripts, multicultural environment, virtual library, national library, google books, blockchain, artificial intelligence.